Revitalizing Higher Education: Strategies to Retain and Attract Talent in Nepal - Sharma, Deepa; Silwal, Binita; Giri, Bishal; Pokharel, Kritima; Dahal, Bikesh; Pandey , Bishesh; Shrestha, Bharat Kumar (International Journal of Educational and Life Sciences, 2024)
Study examines challenges in Nepal's higher education system and proposes strategies to retain talent. Factors driving Nepalese students abroad include education relevance, limited seats, economic considerations, ROI, and political stability. Interviews with education ministry officials suggest dialogue with institutions, addressing limited seats, long-term human capital plans, and education loans. Gaps between rhetoric and action in government strategies are noted. Recommendations include fostering dynamic learning, embracing technology, prioritizing faculty development, and creating inclusive spaces. This research contributes practical insights for policymakers and educators to enhance Nepal's higher education landscape.